1990
DOI: 10.1111/j.1360-0443.1990.tb01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned learning in alcohol dependence: implications for cue exposure treatment

Abstract: A review of the literature pertinent to cue exposure treatment in alcohol dependence is presented. Psychological models of relapse, based on conditioning and social learning theories, are critically evaluated. In particular, attention is drawn to the potential implications for cue exposure research and treatment of an interaction between Pavlovian and operant conditioning, problems with the application of the concepts of arousal and craving and the importance of a systems model to understand physiological resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(120 citation statements)
references
References 110 publications
5
113
0
2
Order By: Relevance
“…This study found that during craving states elicited by a combination of nicotine deprivation and smoking cue exposure, our craving responses tended to covary and thus provided support for an assumption implicit in many theories of craving, such as conditioned withdrawal, conditioned compensatory response, conditioned appetitive motivation, and social learning theory (Drummond, Cooper, & Glautier, 1994;Niaura et al, 1988). As has been suggested with emotional states such as fear, response covariation is more likely to appear during intense, rather than mild, emotional states (Hodgson & Rachman, 1974;Lang, 1984).…”
Section: Discussionmentioning
confidence: 68%
“…This study found that during craving states elicited by a combination of nicotine deprivation and smoking cue exposure, our craving responses tended to covary and thus provided support for an assumption implicit in many theories of craving, such as conditioned withdrawal, conditioned compensatory response, conditioned appetitive motivation, and social learning theory (Drummond, Cooper, & Glautier, 1994;Niaura et al, 1988). As has been suggested with emotional states such as fear, response covariation is more likely to appear during intense, rather than mild, emotional states (Hodgson & Rachman, 1974;Lang, 1984).…”
Section: Discussionmentioning
confidence: 68%
“…Many studies have indicated that passive exposure to alcohol-or drug-associated environmental cues may elicit alcohol/drug-seeking behavior in human addicts after weeks or months of abstinence (Drummond et al, 1990;George et al, 2001). In line with clinical data, ethanol is a strong reinforcer for laboratory animals (Samson et al, 2000), and alcohol-associated cues elicit drug-seeking behavior in animals trained to self-administer alcohol, even after protracted abstinence (Shalev et al, 2002;Wedzony et al, 2003;Bienkowski et al, 2004).…”
Section: Introductionmentioning
confidence: 89%
“…Experiential exercises, including cue exposure, were also included in the treatment protocol. Cue exposure has been used in other substance-using populations and typically involves presenting substance-associated stimuli without the opportunity to engage in the substance using behaviors (Childress et al, 1993;Drummond, Cooper, & Glautier, 1990). In our protocol, stimuli that were used to elicit cravings included cigarette packs, lighters, and imaginal exposure exercises.…”
Section: Physical Addictionmentioning
confidence: 99%